COVID-19 and Sustainable Food Systems: What Should We Learn Before the Next Emergency - Bisoffi, Stefano; Ahrné, Lilia; Aschemann-Witzel, Jessica; Báldi, András; Cuhls, Kerstin; DeClerck, Fabrice; Duncan, Jessica; Hansen, Henning Otte; Hudson, Richard L.; Kohl, Johanna; Ruiz, Begoña; Siebielec, Grzegorz; et al. (Frontiers in Sustainable Food Systems, 2021)
Three key transitions leading to a “safe and just” operating space, with a focus on food systems, emerged during the development of a Foresight study promoted by SCAR (Standing Committee on Agricultural Research1): (a) sustainable and healthy diets for all; (b) full circularity in the use of resources; (c) diversity as a key component of stable systems. As consequence of COVID-19, food emerged again as a central element of life, along with health, after decades in which food security was taken for granted, at least in most developed countries. The COVID-19 outbreak offered the opportunity for a reflection on the importance of resilience in emergencies. Sustainable and healthy diets for all, was shown, during the pandemic, to depend much more on social and economic conditions than on technical aspects of food production and processing. Agriculture and the agro-industry have now a potential to absorb, at least temporarily, workers laid out in other sectors; the pandemic could be an opportunity to re-think and re-value labor relationships in the sector as well as local productions and supply chains. A full circularity in food systems also would benefit from stronger links established at the territorial level and increase the attention on the quality of the environment, leading to the adoption of benign practices, regenerating rather than impoverishing natural resources. Diversity is a key component of a resilient system, both in the biophysical sphere and in the social sphere: new business models, new knowledge-sharing networks, new markets. The three transitions would operate in synergy and contribute to the resilience of the whole food system and its preparation for a possible next emergency. Science can support policy making; however, science needs to be better embedded in society, to have a clear direction toward the grand challenges, to address the social, economic, behavioral spheres, to aim clearly at the common good. We need to re-think the conundrum between competition and cooperation in research, devising ways to boost the latter without sacrificing excellence. We need to improve the way knowledge is generated and shared and we need to ensure that information is accessible and unbiased by vested interests.